INKONSISTENSI PENERAPAN DALUWARSA GUGATAN PHK SATU TAHUN DI PENGADILAN HUBUNGAN INDUSTRIAL: Inconsistency the Application of the One-Year Statute of Limitations for Termination of Employment in the Industrial Relations Court - Refaya Akbar Arasyid; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2026)
The settlement of termination of employment (PHK) disputes in Indonesia is subject to a one-year statute of limitations as regulated under Article 82 of Law Number 2 of 2004 on Industrial Relations Dispute Settlement. This provision aims to ensure legal certainty; however, in the practice of the Industrial Relations Court (PHI), it frequently conflicts with mandatory bipartite negotiations and mediation processes conducted by the Manpower Office, which require a considerable amount of time. This research aims to analyze the problem the application of the one-year statute of limitations for PHK claims and the judges’ flexible approach in judicial practice. This study employs a normative legal research method with a descriptive-analytical nature, using statutory, legal principles, and court decision approaches. The result and conclusion indicate that the application of the statute of limitations in PHK cases remains inconsistent, as judges tend to apply the concept of exclusion of time to the mediation period in order to achieve substantive justice and protect workers as the weaker party. This research concludes that clearer and more uniform normative regulation is required regarding the statute of limitations for PHK claims to balance legal certainty and worker protection.